CLAYS OF THE NAVBAKHOR DEPOSIT, UZBEKISTAN - Mirzaev A.U.; Chinikulov Kh. (My University, 2004)
A new deposit of high-quality bentonites and carbonate–palygorskite clays was discovered in the Paleogene section of the southwestern foothill of Southern Nuratau Range. The bentonites have a substantially montmorillonitic composition. Minor and admixture components are represented by illite, palygorskite, quartz, iron hydroxides, and other minerals. In terms of physicochemical properties, the bentonites are subdivided into the alkaline and alkaline-earth varieties. The carbonate–palygorskite clays possess a calcite–montmorillonite–palygorskite composition. The bentonites and carbonate–palygorskite clays formed in the alkaline medium of a marine basin. The major rock-forming montmorillonite formed as a result of the transformation of structurally similar clay minerals, while calcite and palygorskite are authigenic minerals. The bentonites and carbonate–palygorskite clays have been ascertained as a material suitable for the preparation of drilling muds, as adsorbents for the bleaching of cotton oil and purification of alcoholic products, as ointment bases and the principal component for medicinal preparations, and for other purposes.
Keywords: Navbakhor deposit; Uzbekistan